Effect of input compression and input frequency response on music perception in cochlear implant users. - Halliwell, Emily R.; Jones, Linor L.; Fraser, Matthew; Lockley, Morag; Hill-Feltham, Penelope; McKay, Colette M. (International Journal of Audiology, 2015)
Objective: A study was conducted to determine whether modifications to input compression and input frequency response characteristics can improve music-listening satisfaction in cochlear implant users. Design: Experiment 1 compared three pre-processed versions of music and speech stimuli in a laboratory setting: original, compressed, and flattened frequency response. Music excerpts comprised three music genres (classical, country, and jazz), and a running speech excerpt was compared. Experiment 2 implemented a flattened input frequency response in the speech processor program. In a take-home trial, participants compared unaltered and flattened frequency responses. Study sample: Ten and twelve adult Nucleus Freedom cochlear implant users participated in Experiments 1 and 2, respectively. Results: Experiment 1 revealed a significant preference for music stimuli with a flattened frequency response compared to both original and compressed stimuli, whereas there was a significant preference for the original (rising) frequency response for speech stimuli. Experiment 2 revealed no significant mean preference for the flattened frequency response, with 9 of 11 subjects preferring the rising frequency response. Conclusions: Input compression did not alter music enjoyment. Comparison of the two experiments indicated that individual frequency response preferences may depend on the genre or familiarity, and particularly whether the music contained lyrics.